A first-rate madness : uncovering the links between leadership and mental illness - Ghaemi, S. Nassir (New York : Penguin Press, 2011)
An investigation into the surprisingly deep correlation between mental illness and successful leadership, as seen through some of history's greatest politicians, generals, and businesspeople. "A First-Rate Madness," Nassir Ghaemi, who runs the Mood Disorders Program at Tufts University Medical Center, draws from the careers and personal plights of such notable leaders as Lincoln, Churchill, Gandhi, Martin Luther King, Jr., JFK, and others from the past two centuries to build an argument at once controversial and compelling: the very qualities that mark those with mood disorders- realism, empathy, resilience, and creativity-also make for the best leaders in times of crisis. By combining astute analysis of the historical evidence with the latest psychiatric research, Ghaemi demonstrates how these qualities have produced brilliant leadership under the toughest circumstances. Take realism, for instance: study after study has shown that those suffering depression are better than "normal" people at assessing current threats and predicting future outcomes. Looking at Lincoln and Churchill among others, Ghaemi shows how depressive realism helped these men tackle challenges both personal and national. Or consider creativity, a quality psychiatrists have studied extensively in relation to bipolar disorder.
"A First-Rate Madness" shows how mania inspired General Sherman and Ted Turner to design and execute their most creative-and successful-strategies. Ghaemi's thesis is both robust and expansive; he even explains why eminently sane men like Neville Chamberlain and George W. Bush made such poor leaders. Though sane people are better shepherds in good times, sanity can be a severe liability in moments of crisis. A lifetime without the cyclical torment of mood disorders, Ghaemi explains, can leave one ill equipped to endure dire straits. He also clarifies which kinds of insanity-like psychosis-make for despotism and ineptitude, sometimes on a grand scale. Ghaemi's bold, authoritative analysis offers powerful new tools for determining who should lead us. But perhaps most profoundly, he encourages us to rethink our view of mental illness as a purely negative phenomenon. As "A First-Rate Madness" makes clear, the most common types of insanity can confer vital benefits on individuals and society at large-however high the price for those who endure these illnesses"--Provided by publisher.
The inverse law of sanity -- Creativity. Make them fear and dread us: Sherman ; Work like hell and advertise: Turner -- Realism. Heads I win, tails it's chance ; Out of the wilderness: Churchill ; Both read the same Bible: Lincoln -- Empathy. Mirror neuron on the wall ; The woes of Mahatmas: Gandhi ; Psychiatry for the American soul: King -- Resilience. Stronger ; A first-rate temperament: Roosevelt ; Sickness in Camelot: Kennedy -- Treatment. A spectacular psychochemical succcess: Kennedy revisited ; Hitler amok -- Mental Health. Homoclite leaders: Bush, Blair, Nixon, and others ; Stigma and politics.
Keywords: Depressed persons -- Psychology; Depression, Mental; Leadership -- Psychological aspects; Mentally Ill Persons -- psychology; Mood Disorders; Leadership; Temperament